The Relationship between Capital Structure and Profitability - Velnampy, T.; Niresh, J.A. (My University, 2012)
Capital structure decision is the vital one since the profitability of an enterprise is directly affected by such decision. The successful selection and use of capital is one of the key elements of the firms’ financial strategy. Hence, proper care and attention need to be given while determining capital structure decision. The purpose of this study is to investigate the relationship between capital structure and profitability of ten listed Srilankan banks over the past 8 year period from 2002 to 2009.The data has been analyzed by using descriptive statistics and correlation analysis to find out the association between the variables. Results of the analysis show that there is a negative association between capital structure and profitability except the association between debt to equity and return on equity. Further the results suggest that 89% of total assets in the banking sector of Sri Lanka are represented by debt, confirming the fact that banks are highly geared institutions. The outcomes of the study may guide banks, loan-creditors and policy planners to formulate better policy decisions as far as the capital structure is concerned.